ANALISIS PERBEDAAN HARGA SAHAM DAN VOLUME PERDAGANGAN SAHAM SEBELUM DAN SESUDAH PENGUMUMAN INDONESIAN CSR AWARD - Robert Jao (P3M STMIK Profesional Makassar, 2014)
Abstract This research aims to investigate if there was difference in stock price and trading volume activity before and after the announcement of Indonesian Corporate Social Responsibility Award 2014. This research samples are 11 companies which accept the appreciation of Indonesian CSR Award 2014 that listed in Indonesia Stock Exchange (IDX). The research data that used is secondary data that consists of daily closing price of share and daily trading volume activity with windows date is 5 days before and 5 days after announcement. Hypotheses are tested by Wilcoxon Signed Test. The result of this research proves that there was difference stock price but it did not change trading volume activity before and after Indonesian CSR Award announcement.